Xu Bing: beyond the Book from the Sky - Fraser, Sarah E.; Li, Yu-Chieh (Springer Singapore, 2020)
Acknowledgements -- Introduction -- Reactivating the Tradition -- In Dialogue with Xu Bing -- Audience Participation in Xu Bing’s Works -- Revisiting Ink Art -- Art as Mellorism -- Xu Bing’s Phoenix: An Aesthetic Image of Labor -- Two-dimensional Space: Reconsidering Chinese Conceptualism in the 1980’s -- Thirty Years of Art Criticism on Xu Bing -- The Great Wall of Digital Language: Juxtaposing Tradition and Modernity in Chinese Contemporary Art -- From Small Woodcuts to Experimental Printmaking: Xu Bing in the 1980’s -- Breaking Through ‘Realism:’ On Xu Bing’s Art -- Xu Bing as Landscapist -- Revisiting the Media of Chinese ‘Avant-garde’ in the 1980’s -- Xu Bing’s Background Story Series -- A Global Map of Xu Bing’s Exhibition History 1985-2015 -- A Global Chronicle of Contemporary Chinese Art 1985-2015. .
Keywords: Aufsatzsammlung; Kunst; Interpretation; Rezeption; Xu, Bing; Künstler; China